2009
DOI: 10.1128/aac.00631-09
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Upregulation of a Resistance-Nodulation-Cell Division-Type Multidrug Efflux Pump, SdeAB, upon Exposure to a Biocide, Cetylpyridinium Chloride, and Antibiotic Resistance in Serratia marcescens

Abstract: Serratia marcescens is an important opportunistic pathogen in hospitals, where quaternary ammonium compounds are often used for disinfection. The aim of this study is to elucidate the effect of a biocide on the emergence of biocide-and antibiotic-resistant mutants and to characterize the molecular mechanism of biocide resistance in Serratia marcescens. A quaternary ammonium compound-resistant strain, CRes01, was selected by exposing a wild-type strain of S. marcescens to cetylpyridinium chloride. The CRes01 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 24 publications
(23 reference statements)
5
49
1
1
Order By: Relevance
“…Other studies have demonstrated that a consortium of biofilm organisms is capable of surviving antibacterial agents at higher 11 inoculum levels [4,15,33]. However, S. marcescens is prone to develop multidrug resistance, via spontaneous mutations in the efflux pump genes, under high concentrations of biocide usage [27,28]. Our results failed to confirm biocide resistance in S. marcescens under laboratory conditions suggesting the extracellular polymeric matrix environment of the biofilm provided protection from Alpron™ within the DUWL.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their contrasting
confidence: 75%
See 2 more Smart Citations
“…Other studies have demonstrated that a consortium of biofilm organisms is capable of surviving antibacterial agents at higher 11 inoculum levels [4,15,33]. However, S. marcescens is prone to develop multidrug resistance, via spontaneous mutations in the efflux pump genes, under high concentrations of biocide usage [27,28]. Our results failed to confirm biocide resistance in S. marcescens under laboratory conditions suggesting the extracellular polymeric matrix environment of the biofilm provided protection from Alpron™ within the DUWL.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their contrasting
confidence: 75%
“…Since the molecular identity of the bacterium from DUWL 9 was identified as S. marcescens, which is a typical nosocomial bacterium, considered to be a clinical isolate its likely survival in the clinical DUWL may have been related to the development of biocide resistance [27,28]. Since the dental biocide used to treat the DUWL from which the water sample was taken was Alpron™, and its efficacy was tested in the laboratory on the isolated strain of S. marcescens.…”
Section: Vermiformis Dominates the Duwl Environment [7] And Their mentioning
confidence: 99%
See 1 more Smart Citation
“…SdeAB's function is dependent on the TolC-like OM protein HasF, and sdeB inactivation increases the susceptibility to fluoroquinolones and other drugs listed above (321). Exposure to a biocide (cetylpyridinium chloride) led to a mutational upregulation of SdeAB and thus antibiotic resistance (322). SdeAB expression is controlled by a BadM-type repressor, SdeS (323), and a putative MarA-like regulator, SdeR (321).…”
Section: Serratia Marcescensmentioning
confidence: 99%
“…A more recent study has demonstrated that exposure of a wild-type strain of Serratia marcesens to CPC resulted in the formation of a QAC-resistant mutant exhibiting 2-to 16-fold more resistance to biocides and antibiotics, including CPC, benzalkonium chloride, chlorhexidine gluconate, fluoroquinolones, tetracyclines and chloramphenicol than did wild-type strains (Maseda et al, 2009). …”
Section: Development Of Resistance To Biocides and Therapeutic Antimimentioning
confidence: 99%